1979
DOI: 10.1042/cs0570327
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dietary Lipid in the Regulation of Unconjugated Hyperbilirubinaemia in Gunn Rats

Abstract: 1. The purpose of this study was to characterize the mechanisms of diet-induced hyperbilirubinaemia in Gunn rats with emphasis on the role of lipids, and to examine their relationship with regard to fasting hyperbilirubinaemia. 2. A lipid-free normocaloric diet produced a threefold increase in plasma bilirubin concentration (baseline 109.4 mumol/l), which was maximal by 10 days and thereafter remained constant. The level of hyperbilirubinaemia attained was not influenced by fasting or phenobarbitone, and retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Whitmer and Gollan (4) found that dietary fat must be reduced to an extremely low level (perhaps to 0.6% of the total caloric intake) to produced hyperbilirubinemia in Gilbert's subjects. Lipid-free diets caused unusually high plasma bilirubin concentrations in Gunn rats which are reduced by small lipid supplements (29). In contrast to those observations in humans and rats, fasting plasma bilirubin concentrations in Bolivian squirrel monkeys fed 5% fat (11% of calories) were lower than those fed very low-(0.3%) or high-fat (20%) diets.…”
Section: Discussionmentioning
confidence: 65%
“…Whitmer and Gollan (4) found that dietary fat must be reduced to an extremely low level (perhaps to 0.6% of the total caloric intake) to produced hyperbilirubinemia in Gilbert's subjects. Lipid-free diets caused unusually high plasma bilirubin concentrations in Gunn rats which are reduced by small lipid supplements (29). In contrast to those observations in humans and rats, fasting plasma bilirubin concentrations in Bolivian squirrel monkeys fed 5% fat (11% of calories) were lower than those fed very low-(0.3%) or high-fat (20%) diets.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study there is a high correlation between serum total bilirubin and free fatty acids in horses; this was further improved by the addition of triglycerides to the regression equation. An association between plasma triglycerides and bilirubin is not found in Gunn rats (25). However, plasma free fatty acid concentrations are related to the degree of fasting bilirubinemia in Gunn rats (26) and man (27).…”
Section: Hours Of Refeemngmentioning
confidence: 94%
“…Oral saline o r 400-kcal quantities of mannitol or amino acids do not affect serum bilirubin (31) or free fatty acid concentrations (32,33 . A recent study compared the effects of food deprivation and lipid withdrawal and suggested that these factors may influence bilirubinemia through different mechanisms (25). The mechanism of fasting bilirubinemia is obscure.…”
Section: Hours Of Refeemngmentioning
confidence: 99%
“…30 The present data indicate that plasma UCB levels are almost twice as high in Gunn rats fed a LF diet compared with a HF diet. Gollan et al 45 showed that a fat-free diet increased plasma bilirubin concentrations threefold in Gunn rats. They reported that dietary supplementation with a variety of fats largely reversed the increased hyperbilirubinemia, regardless of their fatty acid chain length or degree of saturation.…”
Section: Discussionmentioning
confidence: 99%